RINT1 Loss Impairs Retinogenesis Through TRP53-Mediated Apoptosis - Gomes, Anielle L.; Matos-Rodrigues, Gabriel E.; Frappart, Pierre-Olivier; Martins, Rodrigo A. P. (Frontiers in Cell and Developmental Biology, 2020)
Genomic instability in the central nervous system (CNS) is associated with defective neurodevelopment and neurodegeneration. Congenital human syndromes that affect the CNS development originate from mutations in genes of the DNA damage response (DDR) pathways. RINT1 (Rad50-interacting protein 1) is a partner of RAD50, that participates in the cellular responses to DNA double-strand breaks (DSB). Recently, we showed that Rint1 regulates cell survival in the developing brain and its loss led to premature lethality associated with genomic stability. To bypass the lethality of Rint1 inactivation in the embryonic brain and better understand the roles of RINT1 in CNS development, we conditionally inactivated Rint1 in retinal progenitor cells (RPCs) during embryogenesis. Rint1 loss led to accumulation of endogenous DNA damage, but RINT1 was not necessary for the cell cycle checkpoint activation in these neural progenitor cells. As a consequence, proliferating progenitors and postmitotic neurons underwent apoptosis causing defective neurogenesis of retinal ganglion cells, malformation of the optic nerve and blindness. Notably, inactivation of Trp53 prevented apoptosis of the RPCs and rescued the generation of retinal neurons and vision loss. Together, these results revealed an essential role for TRP53-mediated apoptosis in the malformations of the visual system caused by RINT1 loss and suggests that defective responses to DNA damage drive retinal malformations.